The Quality of Broiler Chicken Meat Sold in Traditional Market of Jember Regency: Escherichia coli Bacteria Contamination Rate, TPC Test, Water Content, and pH Value - Dharwin Siswantoro; Imam Busthomi; Ujang Suryadi; Agus Hadi Prayitno; Satria Budi Kusuma (Politeknik Pembangunan Pertanian Manokwari, 2023)
The goal of this study was to assess whether the broiler chicken meat sold in Jember Regency's traditional markets complied with the Indonesian National Standard's (SNI) level for Escherichia coli contamination. Sixteen samples of broiler chicken meat were randomly selected (random sampling) from eight traditional markets that met the Jember Regency's requirements for traditional markets. Escherichia coli was examined by inoculating the bacteria on L-EMBA media and then performing a microscopic examination. The parameters of this study were the Escherichia coli bacteria content test, the TPC test, the water content, and the pH value of broiler chicken meat. The binomial test and descriptive analysis were utilized in this study's data analysis. Sixteen samples of broiler chicken meat from traditional markets in the Jember Regency were subjected to binomial tests, and none of the findings revealed the presence of the bacteria Escherichia coli. However, the TPC findings from 16 samples of broiler chicken meat revealed that every one of them above the 1x106 cfu/ml according to SNI requirements. With an average water content of 75.07% and an average pH of 6, broiler chicken meat is an ideal environment for microbial development. Based on the research that has been carried out, it can be concluded that broiler chicken meat in Jember Regency is free from contamination of Escherichia coli bacteria, but the number of TPC is still above the standard.